دراسة مقارنة لأثر صافي الأنشطة التمويلية في صافي أرباح المصارف الإسلامية للفترة (2010-2022) (Journal of Hama University, 2025)
The research aimed to know the impact of net financing activities on the profits of Islamic banks by applying it to bank data The Islamic Levant and Dubai during the period 2010-2022، in line with the rapid financial developments witnessed by Islamic banks، in accordance with their structure and legal framework، in light of their vulnerability to risks، and in accordance with their ability to compete with traditional banks، in addition to the role of Islamic banks in economic growth.      Net financing activities were used as an independent variable and net profits as a dependent variable in both of the aforementioned banks، measuring the effect between the two variables and then comparing the two effects during the years of the study.      Many conclusions were reached، the most important of which are: There is no statistically significant effect at the significance level of 0.05 for net Islamic financing on the net profits of Islamic banks for Dubai Bank.                         Keywords: net Islamic financing activities، net profits، simple linear regression model.